A dynamic model of effective factors on Agile business–IT alignment. Issue 10 (18th November 2019) - Bigdeli, Elaheh; Motadel, Mohammadreza; Toloie Eshlaghy, Abbas; Radfar, Reza
Abstract : Purpose: This paper aims to present a dynamic model based on casual relationships among the most important effective factors on business–IT alignment in Agile businesses by using system dynamics modeling approach. Design/methodology/approach: To study the most important factors on agility and alignment, the data were collected by questionnaires filled by 201 experts and were analyzed by SPSS and PLS. Casual relationships among studied factors and efficiency coefficients of each factor were identified by fuzzy DEMATEL technique and analyzed by MATLAB and EXCELL. Finally, the dynamic model was plotted by VENSIM. Findings: According to the results, only "learning IT capabilities" are the most important casual factor that has the highest influence on the other factors. "Business responding capabilities" take the highest effect from the system, and "business sensing capabilities" are in the next rank. Practical implications: This study underpins effective IT deployment toward developing efficient IT capabilities to gain greater agility. Originality/value: The dynamic capabilities view (DCV) has emerged as an influential theoretical and management framework in modern IS and agility researches. In this regard, we propose a conceptualization of dynamic capabilities in the form of an alignment model. Based on the dynamic capabilities, and on the alignment perspectives found in Henderson and Venkatraman's seminal model, IT alignment is modeled as a process of reconfiguration of the firm's IT and organizational resources, competencies and capabilities.